2022
DOI: 10.1007/s00431-022-04470-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurological assessment of newborns with spinal muscular atrophy identified through neonatal screening

Abstract: The possibility to identify patients with spinal muscular atrophy through neonatal screenings has highlighted the need for clinical assessments that may systematically evaluate the possible presence of early neurological signs. The aim of this study was to use the Hammersmith Neonatal Neurological Examination (HNNE) and a module specifically designed for floppy infants to assess the possible variability of neurological findings in infants identified through neonatal screening. The infants included in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…To date, together with our six newly described patients, a total of 44 patients carrying c.859G>C have been reported worldwide, including a patient recently detected by newborn screening [ 21 , 22 , 23 , 25 , 31 , 32 , 33 , 34 ]. In general population databases, the c.859G>C variant is reported at a frequency of approximately 0.3% with 132 homozygotes detected [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, together with our six newly described patients, a total of 44 patients carrying c.859G>C have been reported worldwide, including a patient recently detected by newborn screening [ 21 , 22 , 23 , 25 , 31 , 32 , 33 , 34 ]. In general population databases, the c.859G>C variant is reported at a frequency of approximately 0.3% with 132 homozygotes detected [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Six patients (all men, 40%, figure 2B) were symptomatic or showed signs suggestive of disease onset at the first visit; the clinical details of these patients have already been reported 12. The median age at the diagnosis of SMA was 6 days of life (range: 5–9, excluding the child with late diagnosis); the turnaround time of the confirmatory test was 1–3 working days; the family was provided with an official report at a median age of 11 days (range: 7–21 days, figure 1).…”
Section: Resultsmentioning
confidence: 77%
“…Patients with two SMN2 or three copies were treated immediately; patients with SMN2 of > 4 were included in a strict clinical follow-up to detect the first signs of the disease (figure 1). 12 According to Italian law, the costs of allowed DMTs are covered by a dedicated national fund for innovative drugs for 3 years following the registration; subsequently, the costs are covered by the regional governments following hospital prescription.…”
Section: Methodsmentioning
confidence: 99%
“…Others have suggested that disease modifier variant testing is also important to further refine the likely prognosis for SMA patients identified through NBS with two or three copies of SMN2 [ 17 ]. As NBS programs and our understanding of the intersection of screening and treatment continue to expand, it is likely that NBS testing will move toward providing as much genetic information as possible to maximize treatment benefits in newborns with SMA [ 41 ]. As the complexity of NBS is increasing, genetic programs in newborns should come along with adequate pre-test genetic counseling to provide more precise information to the families.…”
Section: Newborn Screening For Smamentioning
confidence: 99%